2019
DOI: 10.1186/s13052-019-0702-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between air quality and respiratory pathogens among children in Suzhou City

Abstract: Objective We studied the short-term effects of air pollutant concentrations in Suzhou City on respiratory infections in children of different age groups. Methods We employed clinical data from children hospitalized with respiratory infections at the Children’s Hospital of Soochow University during 2014–2016, and air quality for Suzhou City covering the same period.We investigated the relationships between the air pollutant concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
3
14
0
7
Order By: Relevance
“…This finding was in agreement with the results of previous studies on the association between PM 2.5 and ILI cases in Beijing (Feng et al, 2016), and data on hospital admissions in Guangzhou related with air pollution (Zhang et al, 2014). Zhang et al (2019) assessed the short-term effects of air pollutant concentrations in Suzhou City (China) on respiratory infections in children of different age groups. The results of single-pollutant models showed that PM 2.5 , PM 10 , NO 2 , SO 2 and CO had significant associations with respiratory tract infections in children < 3 years.…”
Section: Association Of Outdoor Air Pollution and Respiratory Virusessupporting
confidence: 91%
“…This finding was in agreement with the results of previous studies on the association between PM 2.5 and ILI cases in Beijing (Feng et al, 2016), and data on hospital admissions in Guangzhou related with air pollution (Zhang et al, 2014). Zhang et al (2019) assessed the short-term effects of air pollutant concentrations in Suzhou City (China) on respiratory infections in children of different age groups. The results of single-pollutant models showed that PM 2.5 , PM 10 , NO 2 , SO 2 and CO had significant associations with respiratory tract infections in children < 3 years.…”
Section: Association Of Outdoor Air Pollution and Respiratory Virusessupporting
confidence: 91%
“…The finding showed that increases in PM 2.5 were associated with increased rates of emergency department visits for influenza (average, 3.9%, range, 2.1-5.6%). Another study has also shown that PM 2.5 , PM 10 , NO 2 , SO 2 and CO were significantly correlated with respiratory tract infections in children under 3 years, and PM 2.5 was significantly correlated with viral respiratory diseases in children under 7 months (Zhang et al, 2019). PM 2.5 is one of the most significant air pollutants in regards to health impacts on chronic diseases, lung diseases and respiratory problems.…”
Section: Introductionmentioning
confidence: 94%
“… 1 ; 2 ; 3 ; 4 ; 5 ; 6 ; 7 ; 8 ; 9 ; 10 ; 11 ; 12 ; 13 ; 14 ; 15 ; 16 ; 17 ; 18 ; 19 ; 20 ; 21 ; 22 ; 23 ; 24 ; 25 ; 26 ; 27 ; 28 ; 29 ; 30 ; 31 ; 32 ; 33 ; 34 ; 35 ; 36 ; 37 ; 38 ; 39 ; 40 ; 41 ; 42 ; 43 ; 44 ; 45 ; 46 ; 47 ; 48 ; 49 ; 50 ; 51 ; 52 .…”
Section: Uncited Referencesunclassified